EVALUATION OF Xylocopa spp. (Hymenoptera: Anthophoridae) AS POLLINATORS IN PASSION FRUIT CULTIVATION (Passiflora edulis var. Flavicarpa Degener) - CAICEDO-R., GUADALUPE; VARGAS-G., HÉCTOR; GAVIRIA-M., JAIME (Revista Colombiana de Entomología, 1993)
With the aim of establishing the number of individuals of Xylocopa spp. required for adequate pollination in Yellow passion fruit, the efficiency of the process was evaluated in a plantation at Ingenio Riopaila (25,5 ha), located at Zarzal (Valle) in the Tropical dry forest. Three representative areas were evaluated, each of them with 48 sq.m. Sampling the number of flowers per plant, observations were made by the "Method of the Specific Time" during 15 days, measuring over the observed individual’s activities such as searching, visit to pollinate and non-pollinate structures, and mean feeding time over pollinated flowers. The pollinated flowers were tagged in order to measure their fructification. Under conditions of 18 flowers/plant/day, on the average, it was found that each Xylocopa uses 22,9% of its timé (12 hours of activity) visiting and feeding on pollinate flowers, which represents 2,75 hours/day in this activity. The feeding time was 5,4 seconds per flower. An individual can visit 1.833 pollinable flowers per day. The observations of fruit set over the visited flowers gave 45% of formed fruits.